Mechanical resistance of granular activated carbon media in drinking water treatment. (24th November 2019) - Philibert, Marc; Zacchi, Calini Moser; Pottier, Christian; Sacareau, Damien; Baudin, Isabelle
Abstract: Organic microcontaminants in resources are a major issue for drinking water treatment plants and granular activated carbon (GAC) adsorption is one of the preferred treatment units used for their removal. GAC particles are small, abrasive and generally have irregular angular shapes. The combination of the particles' characteristics and GAC filters operations leads to a risk of material loss through abrasion between the particles. Mechanical resistance characterization methods were applied to 14 commercially available GAC products, both new and used as well as reactivated, and concluded that commercially available GACs do not present a high risk of material loss though erosion is expected to be continuous throughout the filter's life. The evaluation of the reactivation step showed that it had a significant impact on the parameters to evaluate the mechanical resistance of the GAC but did not result in an increased erosion of the material in operation.